2021
DOI: 10.3389/fendo.2021.712855
|View full text |Cite
|
Sign up to set email alerts
|

Neck Circumference Is Associated With Hyperuricemia in Women With Polycystic Ovary Syndrome

Abstract: ObjectiveTo evaluate the association between neck circumference (NC) and hyperuricemia in women with polycystic ovary syndrome (PCOS).MethodsThis is a cross-sectional study that recruited 601 women with PCOS from January 2018 to January 2021. PCOS was diagnosed according to the Rotterdam definition. Hyperuricemia was defined as serum uric acid level of at least 357 μmol/L.ResultsPCOS females with hyperuricemia had significantly greater values of NC, body mass index (BMI), waist circumference (WC) and hip circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…UA/Cr ratio was positively correlated with BMI, WC, TG, LDL-C, HOMA-IR, and negatively correlated with HDL-C even in subjects with normal serum uric acid levels and different glucose tolerance states [23]. We found a positive correlation between UA/Cr ratio and neck circumference, this is in parallel with Yang et al [24] who identified a positive correlation between neck circumference and hyperuricemia in women with PCOS. Upper body adiposity leads to excess free fatty acid release and high airway pressure with consequent oxidative stress and insulin resistance [25].…”
Section: Discussionsupporting
confidence: 88%
“…UA/Cr ratio was positively correlated with BMI, WC, TG, LDL-C, HOMA-IR, and negatively correlated with HDL-C even in subjects with normal serum uric acid levels and different glucose tolerance states [23]. We found a positive correlation between UA/Cr ratio and neck circumference, this is in parallel with Yang et al [24] who identified a positive correlation between neck circumference and hyperuricemia in women with PCOS. Upper body adiposity leads to excess free fatty acid release and high airway pressure with consequent oxidative stress and insulin resistance [25].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, it contributes to a collection of metabolic abnormalities, including decreased glucose tolerance and insulin sensitivity. Second, recent compelling evidence indicates that NC is independently associated with hyperuricemia in women with PCOS, and elevated serum uric acid levels have been well acknowledged as a risk factor for metabolic risk factors [25]. Third, it has been demonstrated that NC is a reliable indicator for insulin resistance in women with PCOS [13].…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal and metabolic parameters were obtained by analyzing the fasting blood samples after an overnight fast of at least 8 hours during the menstrual period. The assay methods of hormonal and metabolic parameters have been detailed in a previous study [25]. The intra-assay variation was less than 10% and the inter-assay variation was less than 10% for all the assay methods.…”
Section: Anthropometric and Laboratory Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The receiver operating characteristic (ROC) curve was obtained (MedCalc V19) for the display of the constructed models, then the area under the curve (AUC) was used to designate the ROC effect. Moreover, the screening efficacy of potential biomarkers for presence in COVID-19 patients was assessed with the misdiagnosis rate, the missed diagnosis rate, and the Youden Index (YI) ( 23 ). All the screening models were tested using five-fold cross validation as internal validations.…”
Section: Methodsmentioning
confidence: 99%